Logic Circuits Timing Analysis Using Timed Logic Variables - Galupa, Nicolae (European Scientific Journal, ESJ, 2016)
Combinational logic circuit timing analysis is an important issue that all designers need to address. The present paper presents a simple and compact analysis procedure. We follow the guidelines drawn by previous methods, but we shall define new time-dependent logic variables that help us improve their efficiency. By using the methodology suggested, we shall replace a very laborious technique (pure delay circuit + time constants method) with a simpler procedure that can pinpoint the specific conditions for a logic circuit’s anomalous behaviour within a few simple steps. Considering the logic function implemented the methodology presented will require analysis of only a limited number of situations/combinations to determine the presence of an anomalous behaviour. When anomalous behaviour is identified, the methodology provides a clear timing description.